On Certain Spatial Patterns in Perm Region Microtoponymy - Y. V. Zvereva (Tsentr nauchnykh i obrazovatelnykh proektov, 2019)
The relevance of the work is determined by the analysis of microtoponymy of the Perm Region, which is poorly studied. The language models of spatial relations expression on the material of Perm toponymy are considered for the first time. The author dwells on the characteristics of the spatial model of proximity / remoteness in toponymic system of Perm Region. The article determines the main indicators of proximity / remoteness of geographical object from the settlement, these indicators are the attributes дальний / ближний , as well as their partial synonyms окольный / удворный, уличный . It is noted that the idea of remoteness can be expressed indirectly, with the help of attributes of non-spatial nature: дикий , глухой , бедняцкий / поваренный , назёмный , поповский . The paper also analyzes geographical terms that are the parts of microtoponyms that can have the semantics of remoteness. As a rule, these terms are related to slash-and-burn farming system. The author also describes microtoponyms expressing the idea of spatial proximity by means of adjectives formed from the names of settlements and by means of prepositional-case constructions. It is concluded that in the Perm microtoponymy there are the same spatial patterns that exist in other toponymic systems, but some of them are specific.